Mode‐locked diode laser‐based two‐photon polymerisation. Issue 2 (1st January 2020) - Surkamp, N.; Zyla, G.; Gurevich, E.L.; Klehr, A.; Knigge, A.; Ostendorf, A.; Hofmann, M.R.
Abstract : In this Letter, the authors present the construction of three‐dimensional microstructures by two‐photon polymerisation induced by ultrashort pulses of a mode‐locked diode laser. The ultrafast light source is based on a diode laser with segmented metallisation to realise a waveguide integrated saturable absorber. It is subsequently amplified and compressed resulting in ultrashort laser pulses of 440 fs length and average output power of 160 mW at a fundamental repetition rate of 383.1 MHz. These pulses are coupled into a customised two‐photon polymerisation setup. A series of suspended lines were fabricated between support cuboids for testing the process behaviour. A 3D structure with complex features was polymerised to demonstrate the high potential for mode‐locked diode lasers in the field of direct laser writing.